A High Throughput Screening Assay for Fungicidal Compounds against: Cryptococcus neoformans - Rabjohns, Jennifer L. A. (2013)
Cryptococcus neoformans is a pathogenic fungus that causes meningitis world-wide, particularly in HIV-infected individuals. Although amphotericin B is the “gold standard” treatment for cryptococcal meningitis, the toxicity and inconvenience of intravenous injection emphasizes a need for development of new anti-cryptocccal drugs. Recent data from humans and animal studies suggested that a nutrient-deprived host environment may exist in cryptococcal meningitis. Thus, a screening assay for identifying fungicidal compounds under nutrient-deprived conditions may provide an alternative strategy to develop new anti-cryptococcal drugs for this disease. A high throughput fungicidal assay was developed using a profluorescent dye, alamarBlue, to detect residual metabolic activity of C. neoformans under nutrient-limiting conditions. Screening a library of pharmaceutically active compounds (LOPAC) with this assay identified a potential chemical scaffold, 10058-F4 that exhibited fungicidal activity in the low micromolar range. These results thus demonstrate the feasibility of this alamarBlue-based assay for high throughput screening of fungicidal compounds under nutrient-limiting conditions for new anti-cryptococcal drug development.